Identity under the perspective of critical social psychology: revisiting the ways of edification of a theory - Miranda, Sheila Ferreira (2014)
Think about the aspects of identity in contemporary production means to quest for understanding meanings assumed by individuals and attributed to transformations experienced throughout their lives and still one of the greatest theoretical challenges of today to the different areas of the humanities. In the context of a Critical Social Psychology, this debate is especially relevant because the discussion calls for the development of theoretical constructs that contribute to a successful result reading of social reality, taking into account the undisputed political commitment of the theoretical and epistemological intentionality social psychology historically situated. Based on these guidelines, the aim of this study is to revisit the paths taken by the work of Antonio da Costa Ciampa, from a reading of his doctoral thesis toward the theoretical construction of the phrase identity-metamorphosis-emancipation, seeking to clarify the main conceptual and epistemological design of your work. And to assess the analytical potential of the writings of the author, argue that his work constitutes a theory of identity and not just an analytical category, whose building aims, especially, find vanishing points, emancipatory alternatives to the framework of individualism, coercions and dissension caused by the inversion of values in modern societies.